The Halal Perspective on AI Voice Over Usage in Marketing and Advertising: Ethical and Sustainable Insights - Asep Koswara; lina herlina (ASEAN Journal of Halal Study, 2024)
This paper explores the ethical, cultural, and sustainability implications of using AI voiceovers in marketing from an Islamic perspective. AI voiceover technology, which utilizes complex algorithms and deep learning to replicate human voices, has gained popularity for applications in advertising, customer service, and entertainment. While AI voiceovers offer significant benefits such as cost-effectiveness, efficiency, and accessibility, their usage raises concerns regarding ethical standards, environmental impact, and cultural sensitivity. This study highlights how Islamic teachings on justice, respect, and sustainability can guide the responsible use of AI voiceovers. By examining key issues such as energy consumption in AI systems and the importance of cultural inclusivity, this paper emphasizes the need for businesses to adopt practices that align with both ethical and environmental principles. It also stresses the importance of avoiding cultural insensitivity and stereotypes when using AI voices across different regions. The paper concludes with practical recommendations for marketers and suggestions for future research on the long-term impacts of AI voiceovers, offering a balanced approach to integrating this technology in a way that benefits society while upholding Islamic values.